2009
DOI: 10.1158/1078-0432.ccr-09-1352
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear NF-κB p65 Phosphorylation at Serine 276 by Protein Kinase A Contributes to the Malignant Phenotype of Head and Neck Cancer

Abstract: Purpose: Aberrant nuclear activation and phosphorylation of the canonical NF-κB subunit RELA/p65 at Serine-536 by inhibitor κB kinase is prevalent in head and neck squamous cell carcinoma (HNSCC), but the role of other kinases in NF-κB activation has not been well defined. Here, we investigated the prevalence and function of p65-Ser276 phosphorylation by protein kinase A (PKA) in the malignant phenotype and gene transactivation, and studied p65-Ser276 as a potential target for therapy. Experimental Design: Pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 46 publications
(51 reference statements)
2
42
0
Order By: Relevance
“…Moreover, inhibition of PKA pathway by H89 could abolish the cAMP-mediated aromatase induction through up-regulating brca1 expression (44). Similar to our study, a number of previous reports support the possibility that PKA signaling contributes to the constitutive NF-B activation (45)(46)(47). In this study, we demonstrated that NF-B inhibitor BAY11-7082 repressed MDA-MB231 cell proliferation by blocking IKK, and PKA inhibitor H89 further augmented this inhibitory action (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, inhibition of PKA pathway by H89 could abolish the cAMP-mediated aromatase induction through up-regulating brca1 expression (44). Similar to our study, a number of previous reports support the possibility that PKA signaling contributes to the constitutive NF-B activation (45)(46)(47). In this study, we demonstrated that NF-B inhibitor BAY11-7082 repressed MDA-MB231 cell proliferation by blocking IKK, and PKA inhibitor H89 further augmented this inhibitory action (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For example, phosphorylation of NF-κB at Ser276 by PKA stimulates NF-κB transcriptional activity by promoting the interaction of NF-κB with the coactivator CBP/p300 (62). NF-κB p65 phosphorylation at Ser276 by PKA activates NF-κB and contributes to the malignant phenotype of head and neck cancer (84). It has been also shown that PKA-Cα activates NF-κB signaling via phosphorylating p65 at Ser276 in an IKKβ-dependent but cAMP-independent manner (61).…”
Section: (E-h) Beas-2b Cells Were Transfected With Sirna (E and F) Ormentioning
confidence: 99%
“…ICAM1 gene promoters contain several NF-kB response elements (Stade et al 1990). Most importantly, PKA has been reported to phosphorylate the p65 subunit of NF-kB, which contributed to the binding of NF-kB to the ICAM1 gene promoter (Arun et al 2009). To address the question whether NF-kB participated in Ucn1-induced ICAM1 regulation, we used an NF-kB inhibitor, PDTC.…”
Section: Pka-creb Participated In the Signaling Events Leading To Indmentioning
confidence: 99%